“COMING TOGETHER” (Batanai): Learning from Zimbabwe’s experiences with community biodiversity conservation, participatory crop improvement and climate change adaptation - Vernooy, Ronnie; Netnou-Nkoana, Noluthando Caroline; Mokoena, M.; Sema, R.; Tjikana, Thabo T.; Kasasa, P.; Mbozi, H.; Mushonga, J.; Mushita, A. (Bioversity International, 2019)
This brief presents the findings and lessons learned of a study tour by a team from the Department of Agriculture, Forestry and Fisheries of South Africa to neighbouring Zimbabwe, to learn about the roles of Farmer Field Schools, functions and operations of community seedbanks and various forms of participatory crop improvement, promoted by the Community Technology Development Organisation of Zimbabwe.